Tarsometatarsal Joint Preparation using a Modified Dorsal Approach vs Standard Approach: A Cadaver Study. Issue 4 (November 2022) - Shah, Ashish; Murali, Sudarsan; Littlefield, Zachary; Young, Sean M.; Patch, David A.; Jacob, Roshan; Luque-Sanchez, Kevin S.; Reed, Logan; Elphingstone, Joseph
Category: Midfoot/Forefoot Introduction/Purpose: Lisfranc injuries are a relatively common midfoot injury involving the tarsometatarsal (TMT) joint. Surgical fixation typically involves open reduction with internal fixation or primary arthrodesis of the joint(s). The standard surgical approach to the TMT joint involves two dorsal incisions however, a recent study has suggested the use of a modified single dorsal incision approach. The goal of this paper is to compare the total surface area of the joint that can be prepared for primary arthrodesis of the TMT using the standard vs modified single dorsal approach. Methods: Ten fresh frozen below-the-knee cadaver specimens were randomly assigned to receive either the standard or modified dorsal single incision operative approach to the TMT joint. Prior to initiating the study, specimens were inspected with fluoroscopic radiographs for preexisting pathology or prior surgical intervention. The joint surface was visualized and then underwent articular preparation as for a joint fusion. After adequate joint preparation, the TMT joint was disarticulated and the surface was photographed for image analysis. Using ImageJ, articular joint surface preparation areas were measured by two blinded reviewers. to assess the joint surface preparation and this was compared by surgical approach. Results: After ImageJ and Mann-Whitney U statistical analysis, there was no significant difference in the amount of joint prepared when comparing the standard versus modified dorsal approach for the first three TMT joints (p= 0.548, p=0.310, p= 0.548). The percentage of joint preparation utilizing the standard dorsal approach versus the modified dorsal approach for TMT joints one through three are as follows (percentages utilized are listed as the median value with its correlating range): First TMT- 67.6% (range 26%) by the standard approach versus 71.7% (range 9%) by the modified dorsal approach, second TMT- 67.9% (range 24%) versus 65.7% (range 12%), and third TMT- 65.9% (range 42%) versus 59.6% (range 24%). Table 1 summarizes our results between each operative approach. Conclusion: With our findings, we demonstrate that a modified single dorsal approach to the Lisfranc joint provided comparable joint preparation for primary arthrodesis as the standard dual incision approach. However, the modified dorsal approach may be beneficial in that it avoids creating a skin bridge which has potential for necrosis with the standard two incision approach. The authors believe the comparable joint preparation combined with its potential to alleviate soft tissue complications make the modified dorsal approach a viable surgical approach for a TMT arthrodesis.